2018
DOI: 10.1186/s12888-018-1766-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body mass index, binge eating disorder and suicidality

Abstract: BackgroundWhile restrictive and compensatory eating disorders (e.g. anorexia and bulimia) are associated with elevated risk of suicide, less is known about binge eating disorder (BED). There is suggestive evidence of a U-shaped relationship between body mass index (BMI) and completed suicide, but fewer studies on suicidal ideation or attempts. This study examined the association between BED, BMI, and suicidality, and assessed whether these relationships varied by gender.MethodsData come from the Collaborative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 40 publications
4
32
2
Order By: Relevance
“…In addition to the student status, gender can be a factor influencing the occurrence of ED [42]. Research findings indicate that AN, BN, and BED are more commonly found among women than men [43][44][45][46]. Similarly, in our study, more women showed the symptoms of ED.…”
Section: Discussionsupporting
confidence: 67%
“…In addition to the student status, gender can be a factor influencing the occurrence of ED [42]. Research findings indicate that AN, BN, and BED are more commonly found among women than men [43][44][45][46]. Similarly, in our study, more women showed the symptoms of ED.…”
Section: Discussionsupporting
confidence: 67%
“…Our clinical observations are supported by current literature showing that medical and social challenges worsen with increasing BMI [21,[39][40][41][42]. For instance, as BMI increases there is a higher prevalence of binge eating [43,44], social discrimination [39] and other co-morbid conditions [8,9], all of which are known contributors to co-morbid psychological conditions such as anxiety and depression [45][46][47][48][49]. The presence of any one of these factors strongly predicts poor adherence to dietary and lifestyle treatments for obesity [50][51][52].…”
Section: Introductionsupporting
confidence: 79%
“…The lack of any direct association between suicidal behaviour and BMI in our sample could be understood in terms of the recent findings of population‐based studies. These studies indicated that suicidal behaviour is higher among underweight individuals (BMI < 20 kg/m 2 ) and people with extreme obesity (BMI ≥ 35 kg/m 2 ) which indicate a U‐shaped or curvilinear relationship . This complex type of relationship is difficult to investigate in our sample, which mainly comprised individuals with an average BMI with a few overweight exceptions.…”
Section: Discussionmentioning
confidence: 87%